T53. NEUROPHYSIOLOGICAL AND BEHAVIORAL EFFECTS OF THE STIMULATION OF NICOTINIC RECEPTORS AND NON-INVASIVE BRAIN STIMULATION IN PATIENTS WITH SCHIZOPHRENIA: STUDY DESIGN AND METHODOLOGY OF A RANDOMIZED CONTROLLED TRIAL. (18th May 2020) - Güler, Duygu; Pross, Benjamin; Nitsche, Michael; Padberg, Frank; Falkai, Peter; Hasan, Alkomiet
Abstract: Background: Tobacco dependence is the most common substance use disorder in schizophrenia patients. Research suggests that prevalence rates for patients with schizophrenia are 40 to 80 percent. It is believed that these patients smoke to improve cognitive deficits. This assumption is supported by several neurophysiological and behavioral studies. The aim of the current study is to assess the physiological fundamentals and the behavioral effects of smoking in patients with schizophrenia. Methods: The present randomized double-blind and controlled study is ongoing and focusses on enhancing cognitive functioning in schizophrenia patients. Nicotinic receptors of participating patients are stimulated by the substance varenicline. The resulting changes are assessed by non-invasive brain stimulation (NIBS) and cognitive performance tests. Additionally, anodal transcranial direct current stimulation (a-tDCS) is applied for inducing plasticity to examine the interaction between tobacco consumption and brain stimulation. The treatment consists of twice daily 1 mg of varenicline (or placebo) and 20-minute a-tDCS (or sham tDCS) over a period of five days. Sixty patients with schizophrenia will be recruited for this pilot study. Results: This is a double-blind study. Therefore no results can be shown so far. To this date 18 patients have been recruited (female = 6). There haven't been major side effects and patients are tolerating the interventions well. Discussion: During the conference we will present the concept and design of the combined "varenicline x tDCS" trial for the treatment of cognitive deficits in schizophrenia.